KETAHANAN ENAM JENIS KAYU TERHADAP JAMUR PELAPUK - Sihati Suprapti; Djarwanto (BRIN Publishing, 2012)
Six wood species namely huru kacang wood (Neolitsea triplinervia Merr.), beleketebe (Sloanea sigun Szysz.), tunggereuk (Castanopsis tunggurrut A.DC.), ki endog (Acer niveum Bl.), buru mentek (Lindera polyantha Borrl.) and neem (Azadirachta indica Juss.), were evaluated its resistance property against nine fungal attack using Kolle-flash methods. Samples of every wood species were divided radially into two groups, namely outer and inner parts of log. Results indicated that A. indica belongs to resistant wood (class II), C. tunggurrut and L. polyantha were moderately resistant (class III), while, N. triplinervia, S. sigun and A. niveum were not resistant (class IV). Comparing of those two samples groups, the weight loss of the inner part was lower i.e. 8.26%, classified as moderately resistant (class III) than that of the outer part logs i.e. 12.4%, classified as not-resistant wood (class IV) to the fungal attack. The highest weight loss was occurred on the outer part log of N. triplinervia exposed to Pycnoporus sanguineus HHBI-324 (54.8%).